ANALISIS PENGARUH PEMBERDAYAAN KARYAWAN TERHADAP KEPUASAN KERJA DI PT SDV LOGISTIC - Francisca Hermawan; Eric Candra (Universitas Ahmad Dahlan, 2014)
Human resource development, knowledge and technology hold an important role in reaching company goal, therefore employee empowerment to perform well needs to be maximally implemented. This research is made to fi nd out if there is any signifi cant impact between employee empowerment and job satisfaction at PT SDV logistic. There are 3 variables used in this empowerment: meaning, self-determination, and impact. Datas used in this research are premier datas with questionnaires and secondary datas obtained from the company. Population in this research is all PT SDV Logistic employees and number of sampling used is 50 respondents, using convenience sampling method. Research result shows that employee empowerment has simultaneous impact to job satisfaction, but partially has no impact on job satisfaction.